2005
DOI: 10.1016/j.appdev.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescents' understanding and reasoning about asylum seeker peers and friendships

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. AbstractThe present study examined ethnically Dutch preadolescents' understanding and reasoning about asylum seeker peers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…Previous research supports this assertion and indicates that adolescent youth perceive differential treatment from same-age peers (DuBois, Burk-Braxton, Swenson, Tevendale & Hardesty, 2002;Fisher et al, 2000;. Peer racial discrimination manifests in multiple ways, including intentional or overt social exclusion, teasing, hitting, and unfair treatment based on ethnic group membership (Brown & Bigler, 2005;Chavous et al, 2008;Greene et al, 2006;Rosenbloom & Way, 2004;Verkuyten & Steenhuis, 2005;. The ethnic and racial hierarchies that emerge in classroom-based sociometric research (Graham, Taylor, & Hudley, 1998;Verkuyten & Kinket, 2000), in which ethnic minorities tend to have lower status and are ascribed less favorable characteristics when rated by peers, also suggests that implicit negative group stereotypes operate within same age-peer groups.…”
Section: Racial Climate and Schoolingsupporting
confidence: 54%
“…Previous research supports this assertion and indicates that adolescent youth perceive differential treatment from same-age peers (DuBois, Burk-Braxton, Swenson, Tevendale & Hardesty, 2002;Fisher et al, 2000;. Peer racial discrimination manifests in multiple ways, including intentional or overt social exclusion, teasing, hitting, and unfair treatment based on ethnic group membership (Brown & Bigler, 2005;Chavous et al, 2008;Greene et al, 2006;Rosenbloom & Way, 2004;Verkuyten & Steenhuis, 2005;. The ethnic and racial hierarchies that emerge in classroom-based sociometric research (Graham, Taylor, & Hudley, 1998;Verkuyten & Kinket, 2000), in which ethnic minorities tend to have lower status and are ascribed less favorable characteristics when rated by peers, also suggests that implicit negative group stereotypes operate within same age-peer groups.…”
Section: Racial Climate and Schoolingsupporting
confidence: 54%
“…The shared and normative perception of these groups-reinforced by media representationsis uniformly negative, homogenous, agentic, and therefore also threatening (Das et al, 2009;Verkuyten, 2011). Visible * politicized * high entitativity ?…”
Section: Visible * Politicized * Low Entitativity ? Veiled Prejudicementioning
confidence: 99%
“…Nesdale (2004) has shown that an awareness of group identity emerges prior to group preference and forms of group prejudice. As children get older, they bolster their sense of social identity by excluding outgroup others from their social ingroup (Nesdale, 2004;Verkuyten & Steenhuis, 2005). An important point demonstrated by Nesdale (2004) is that children do not automatically dislike peers from outgroups.…”
Section: Developmental Theories Of Social and Group Identitymentioning
confidence: 98%